THE ROLE OF REAL ESTATE CADASTRE IN LAND RESOURCE MANAGEMENT IN THE REPUBLIC OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This study explores the critical role of the real estate cadastre in land resource management in Uzbekistan, particularly focusing on its modernization and integration with advanced technologies. The research investigates the impact of digitalization, Geographic Information Systems (GIS), blockchain, and artificial intelligence (AI) on improving land administration, enhancing transparency, and reducing corruption. The findings highlight the ongoing digitalization efforts in Uzbekistan’s land cadastre system, with over 15 million land plots already registered in the Unified State Register of Real Estate (USRE). By 2030, nearly 90% of the land data is expected to be digitized, promising significant improvements in land valuation, tax administration, and land dispute reduction. The study emphasizes the importance of these reforms for sustainable land use, urban planning, and agricultural efficiency. Additionally, it draws on global best practices from countries like Germany, South Korea, and Turkey, offering valuable insights for accelerating Uzbekistan’s cadastre modernization. The research concludes that Uzbekistan’s cadastre reform is essential for enhancing economic growth, ensuring environmental sustainability, and attracting investments.